Synthesis and characterization of high-softening-point methylene-bridged pitches by visible light irradiation assisted free-radical bromination. (December 2015) - Ge, Chuanzhang; Yang, Haixiao; Miyawaki, Jin; Mochida, Isao; Yoon, Seong-Ho; Qiao, Wenming; Long, Donghui; Ling, Licheng
Abstract: A novel methylene-bridged polymeric pitch was successfully synthesized from 1-methylnaphthalene (1-MNP) using bromine as a sacrificial agent for C–C bond construction. 1-MNP was reacted with bromine in the presence of strong visible light irradiation (40–70 kcal/mol), yielding exclusively side-chain substituted 1-methylnaphthalene (M-Br). After a thermal dehydrobromination/polycondensation reaction at 200–270 °C, high quality carbonaceous isotropic pitches with a softening point of 196–250 °C were obtained. The optimized factors influencing the photobromination, including reaction temperature, substrate concentration and properties of solvents were determined. The dehydrobromination reaction kinetic followed a pseudo-first-order reaction model with apparent reaction activation energy of 122.6 kJ/mol. The as-prepared polymeric pitches consisted of numbers of repeated monomers with a linear structure of methylene bridged naphthalene rings. The unique structure of the pitches resulted in high value of C/H ratio, high molecular weight and 100% soluble in toluene. Moreover, the pitches exhibited very low viscosity at temperatures near the softening point, and their viscosities experienced a unique transition from shear-thinning to shear-thickening and then to shear-thinning process. The coke obtained from short molecular pitch by carbonizing at 550 °C show an anisotropic phase of flow domains both in atmospheric pressure and pressured conditions.